Adults' expectations on children's earthquake-related emotions and coping strategies. Issue 5 (28th May 2021) - Raccanello, Daniela; Barnaba, Veronica; Rocca, Emmanuela; Vicentini, Giada; Hall, Rob; Burro, Roberto
ABSTRACT: Natural disasters such as earthquakes have a highly traumatic impact on psychological functioning. Recently, the study of children's earthquake-related emotions and coping strategies has gathered attention. However, little is known on the corresponding adults' representation, adults who in case of disasters are frequently key informants on children's reactions. Examining the influence of earthquake experience, we explored adults' expectations on children's earthquake-related emotions and coping strategies. The participants were 572 Italian university students. Referring to what happens during and after earthquakes, they were asked to list children's (a) expected emotions, and (b) coping strategies for diminishing fear and sadness. We coded (a) number of fear, sadness, and anger terms; (b) presence of 13 coping strategies. We used Generalized Linear Mixed Models. Fear was more frequent than sadness, and more frequent during vs. after earthquakes (and vice versa for sadness). Some coping strategies were reported rarely, while others were more salient (i.e. problem-solving, information-seeking, self-reliance, support-seeking, and accommodation). Earthquake experience had a marginal impact. Our findings enable us to deepen knowledge on the emotional representation of earthquakes. At an applied level, they can help professionals to develop training programs aimed at increasing children's emotional preparedness.